Self/made ebook - Groom, Mat (Self/Made (2018)., 2019)
When chaos besieges the kingdom of Arcadia, warrior Amala Citlali uncovers a shocking truthshe's a non-player character in an advanced video game. With her very existence at stake, Amala embarks on a journey across worlds to escape her prison, find her creator, and demand answers to the fundamental questions of her existence. In his debut editorial role, comics veteran KYLE HIGGINS guides this intimate story of self-discovery that takes readers to lands of high fantasy, futuristic science fiction and beyond. Collects SELF/MADE #1-6. Author: Mat Groom. Illustrator: Eduardo Ferigato, Marcelo Costa . 2019 Mathew Groom & Eduardo Ferigato.